Activated circulating T follicular helper cells and skewing of T follicular helper 2 cells are down-regulated by treatment including an inhaled corticosteroid in patients with allergic asthma - Satsuki Miyajima; Katsunori Shigehara; Ryuta Kamekura; Hiromi Takaki; Hayato Yabe; Ippei Ikegami; Yuichiro Asai; Hirotaka Nishikiori; Hirohumi Chiba; Eiji Uno; Hiroki Takahashi; Shingo Ichimiya (Allergology International, 2020)
Background: CXCR5+ T follicular helper (TFH) cells primarily promote B cells to produce an antigen-specific antibody through germinal centers (GCs). TFH cells exist in circulation, and circulating(c) TFH2 cells, a subset of cTFH cells, are able to help naïve B cells produce IgE in healthy individuals. Conversely, IL-10-producing regulatory B (Breg) cells inhibit an accelerated immune response. Methods: We investigated the roles of cTFH cells and cBreg cells based on a TH2 response in patients with atopic asthma (AA). Thirty-two patients with AA and 35 healthy volunteers (HV) were enrolled. We examined cTFH cells including their subsets, their expression of ICOS and PD-1, and cBreg cells by flow cytometry and their associations with clinical biomarkers. Plasma levels of CXCL13, which is a counterpart of CXCR5, were also measured using ELISA. Results: In patients with AA, cTFH2 cells were increased and cTFH1 cells were decreased compared with those in HV. The expression levels of ICOS on cTFH and their subset cells were elevated and Breg cells were greatly decreased. The plasma levels of CXCL13 in patients with AA were significantly elevated and correlated well with the cTFH2/cBreg ratio. These cells were examined in 10 patients AA before and after inhaled corticosteroid (ICS) treatment. Interestingly, the percentages and numbers of TFH2 and ICOS+ cTFH cells declined after ICS treatment together with improvements in symptoms and clinical biomarkers. Conclusions: The percentages and numbers of cTFH2 and ICOS+ cTFH cells might be useful as biomarkers of TH2 typed airway inflammation in patients with AA. Keywords: CXCL13, ICS, IgE, Regulatory B cell, T follicular helper cell